The last terms must multiply to the last terms (confusing)
example
if ax^3+bx^2+c+d=(ex+f)(gx+h)(jx+k) then
d=fhk
so
70 is last term
we got 2 and 5
2*5*?=70
10*?=70
divide by 10
?=7
the missing number is 7
For this question you can say:
-8 -11q = -9q +6
so now you can add +9q on both sides and +8 on both sides of the equation:
-11q + 9q = 8 + 6
-2q = 14
q = 14/-2
q = -7 :)))
I hope this is helpful
have a nice day
X-12 will give the other number
Answer:
We conclude that:
f(a) + 5 = a² + 8a - 5
Step-by-step explanation:
Given
The function is given by
f(x) = x²+8x-10
To determine
f(a)+5
In order to determine f(a)+5, first, we need to determine f(a).
Now substitute x = a in the function f(x) = x²+8x-10
f(a) = (a)² + 8(a) - 10
f(a) = a² + 8a - 10
Thus,
f(a) + 5 = (a² + 8a - 10) + 5
f(a) + 5 = a² + 8a - 5
Therefore, we conclude that:
f(a) + 5 = a² + 8a - 5
Answer:
50°
Step-by-step explanation:
65 + 65 +C = 180
130+C = 180
C = 180 - 130 = 50